Flood conversation in social media space: between politicisation and poor flood governance / Mustabsyirotul Ummah Mustofa, M. Arief Virgy and Ahmad Mikail - Mustofa, Mustabsyirotul Ummah; Virgy, M. Arief; Mikail, Ahmad (Faculty of Communication & Media Studies, 2024)
Flooding is one of the natural disasters that often occurs in Indonesia during the rainy season. Whenever a flood occurs, people comment on social media to disseminate information related to floods or criticise the government for handling floods. This research analyses how public conversations on social media related to flooding in Indonesia in the period 2021-2024 on X social media. The analysis was conducted using the concept of flood governance to see what the direction of flood conversations on social media X is, especially those related to criticism of governance. The research used a qualitative method with content analysis. Data on floodrelated conversations on X was retrieved using the advanced search feature. The data obtained was later analysed using the concept of flood governance to see whether the conversation leads to criticism of governance or is more inclined to political sentiment. The findings show that the conversations that emerged on social media X related to flooding led to poor flood governance in Indonesia. The dimensions that appear most often are related to community-based and participatory approaches, rules, regulations and governance, and finally actors and relationships between actors. In every reaction to flooding, people on social media often link this issue as an election commodity. The most discussed issue was related to the performance of Anies and Ganjar, who were the most likely gubernatorial candidates at the time, and thus the target of public criticism.